Isotherm, kinetics and ANN analysis of methylene blue adsorption onto nitrogen doped Ulva lactuca Biochar - Amany G. M. Shoaib; Murat Yılmaz; Amany El Sikaily; Mohamed A. Hassaan; Mohamed A. El-Nemr; Ahmed El Nemr (Scientific Reports)
Abstract This study investigates the removal of methylene blue (MB) dye from aqueous solutions using a novel adsorbent, green algae (Ulva lactuca)-derived biochar-ammonia (NDULB), produced through activation with 85% sulfuric acid and hydrothermal treatment with ammonium hydroxide. The characterization of NDULB was carried out through various techniques, including BET surface area analysis and scanning electron microscopy, confirming its high surface area and effective porosity for dye adsorption. This work thoroughly examines the effects of initial MB dye concentration, solution pH, contact time, and NDULB dose on adsorption. The adsorption data were modeled using Langmuir, Freundlich, Tempkin, and Dubinin-Radushkevich isotherms, with the Freundlich model showing the best fit, indicating multilayer adsorption on a heterogeneous surface. According to the investigation’s findings, with an initial MB concentration of 200 ppm and an NDULB dosage of 1.25 g L−1, the adsorption capacity at equilibrium (q e ) is 966.31 mg g−1. Kinetic analysis revealed that the pseudo-second-order model provided the best fit for the experimental data, suggesting chemisorption as the dominant adsorption mechanism. The artificial neural network modeling has been studied and reported. The study clarifies the effects of multiple variables on adsorption, which might lead to key insights to enlighten the development of effective wastewater treatment strategies. The study demonstrates that NDULB offers a promising, sustainable alternative for MB dye removal in wastewater treatment, with significant implications for large-scale application.